2013
DOI: 10.1161/atvbaha.113.301467
|View full text |Cite|
|
Sign up to set email alerts
|

Basilar Artery Diameter Is an Independent Predictor of Incident Cardiovascular Events

Abstract: In this study, we investigated the association between BA diameter and CSVD and cerebral large-vessel diseases through brain MRI and prospectively investigated the predictive value of BA diameter for subsequent cardiovascular events in patients with atherosclerotic risk factors. Materials and MethodsMaterials and Methods are available in the online-only Supplement.© 2013 American Heart Association, Inc. Objective-Basilar arterial (BA) dolichoectasia is associated with cerebral small-vessel disease and stroke. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 25 publications
4
51
2
1
Order By: Relevance
“…7 A relationship between IADE and a higher incidence of coronary events has been reported. 3,8 This finding raises the possibility that muscular arteries (such as coronary and basilar arteries) may simultaneously dilate and remodel in several arterial beds. 9 We performed a case-control study to investigate the coexistence of CAE and IADE in a large consecutive autopsy database.…”
mentioning
confidence: 99%
“…7 A relationship between IADE and a higher incidence of coronary events has been reported. 3,8 This finding raises the possibility that muscular arteries (such as coronary and basilar arteries) may simultaneously dilate and remodel in several arterial beds. 9 We performed a case-control study to investigate the coexistence of CAE and IADE in a large consecutive autopsy database.…”
mentioning
confidence: 99%
“…Traditional atherosclerotic risk factors (eg, hypertension, age) and consequences (stroke, ischemic heart disease, intracranial large and small vessel disease) were predictive (blue boxes) of basilar artery dilation in the article by Tanaka et al 15 Both vascular risk factors and basilar artery dilation independently predict new cardiovascular events (red arrows and red box), but basilar artery dilation does not independently predict new cerebrovascular events. This implies underlying connections between basilar and coronary disease.…”
Section: New Cardiovascular Eventsmentioning
confidence: 95%
“…The study by Tanaka et al 15 reported in this issue of Arteriosclerosis, Thrombosis, and Vascular Biology examines basilar artery dilation as a possible forme fruste of dolichoectasia and demonstrates the importance of this nonatherosclerotic intracranial vessel pathology for systemic vascular risk. In their prospective imaging study, they show that basilar artery dilation at baseline is a significant predictor of future vascular events, especially coronary events.…”
Section: See Accompanying Article On Page 2240mentioning
confidence: 96%
See 2 more Smart Citations